2020
DOI: 10.3389/fmicb.2020.00351
|View full text |Cite
|
Sign up to set email alerts
|

The Yersinia Phage X1 Administered Orally Efficiently Protects a Murine Chronic Enteritis Model Against Yersinia enterocolitica Infection

Abstract: Yersinia enterocolitica is generally considered an important food-borne pathogen worldwide, especially in the European Union. A lytic Yersinia phage X1 (Viruses; dsDNA viruses, no RNA stage; Caudovirales; and Myoviridae) was isolated. Phage X1 showed a broad host range and could effectively lyse 27/51 Y. enterocolitica strains covering various serotypes that cause yersiniosis in humans and animals (such as serotype O3 and serotype O8). The genome of this phage was sequenced and analyzed. No toxin, antibiotic-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
2
16
0
2
Order By: Relevance
“…TNF-α, IL-1β, and IFN-γ expressions in the blood exhibited significantly lower levels at 18 h compared with the control groups. The phenomenon is similar to the cytokine secretion of phage X1 (Xue et al, 2020) and phage VB-SavM-JYL01 (Ji et al, 2019) in the treatment of Yersinia and S. aureus. Some studies have shown that phages have anti-inflammatory properties that reduce the secretion of pro-inflammatory factors.…”
Section: Discussionsupporting
confidence: 54%
“…TNF-α, IL-1β, and IFN-γ expressions in the blood exhibited significantly lower levels at 18 h compared with the control groups. The phenomenon is similar to the cytokine secretion of phage X1 (Xue et al, 2020) and phage VB-SavM-JYL01 (Ji et al, 2019) in the treatment of Yersinia and S. aureus. Some studies have shown that phages have anti-inflammatory properties that reduce the secretion of pro-inflammatory factors.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, the number of Y. enterocolitica in mice colon and caecum tissues was reduced to approximately 10 3 CFU/g after 18 h compared with 10 7 CFU/g in the mice without phage treatment. These results indicate that phage X1 is a promising candidate to control infection by Y. enterocolitica in vivo (Xue et al 2020).…”
Section: Genus Yersiniamentioning
confidence: 76%
“…Preliminary research on this group of phages was conducted in the second half of the twentieth century and was based on phage typing and electron microscopy observations. Further reports focussed on more specific data including morphology of phage particles, the host range, genome sequence, and identification of the receptors involved in host recognition (Leon-Velarde et al 2019;Xue et al 2020) Application of Y. enterocolitica specific phages, especially as part of phage therapy, has rarely been reported. Xue et al (2020) discovered the new Yersinia enterocolitica specific phage X1, which may be considered a possible agent for phage therapy.…”
Section: Genus Yersiniamentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Gastrointestinal delivery (Tanji et al, 2005;Capparelli et al, 2006;Raya et al, 2006;Sheng et al, 2006;Niu et al, 2008;Rozema et al, 2009;Bach et al, 2009;Jamalludeen et al, 2009;Mai et al, 2010;Stanford et al, 2010;Maura et al, 2012;Jaiswal et al, 2013;Abdulamir et al, 2014;Jaiswal et al, 2014;Jun et al, 2014;Mai et al, 2015;Nale et al, 2015;Sarker et al, 2016;Nikkhahi et al, 2017;Yen et al, 2017;Zhao et al, 2017;Vahedi et al, 2018;Bhandare et al, 2019;Dallal et al, 2019;Dissanayake et al, 2019;Xue et al, 2020) 26 ( 36) (Sarker et al, 2017;Corbellino et al, 2019)…”
Section: (17)unclassified